The analysis of household surveys: a microeconometric approach to development policy - Deaton, Angus (Baltimore, MD : Published for the World Bank [by] Johns Hopkins University Press, 1997)
This book is about the analysis of household survey data from developing countries and about how such data can be used to cast light on a range of policy issues.
Includes bibliographical references (p. 439-462) and indexes.
gau 12/12/13
Loans
Keywords: Household surveys -- Developing countries -- Methodology; Developing countries -- Economic conditions -- Econometric models